PELAKSANAAN PEMBINAAN KESEHATAN LINGKUNGAN DI SEKOLAH DASAR WILAYAH KERJA PUSKESMAS BANDAR KHALIPAH KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG TAHUN 2013 - SURYANI HARAHAP; nurmaini *; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
School Health Efforts (UKS) is an effort to supervise and develop healthylifestyle habits that are integrated through of health education, health services, andsupervising of environmental health. The UKS program is one of the programdevelopment of primary health care which is targeted at elementary school student,because in such age group is very vulnerable to health problems. The elementary schoolis an institution that is well organized to educate, and improve the quality of humanresources, whether physical, mental, moral, and intellectual. Supervising ofenvironmental health which aims to improve the quality of healthy life and the healthstatus of student as well as to create a healthy environment to enable growth andoptimal student development.This research aims to identify the implementationt of the supervising ofenvironmental health (planning, training and surpervision) at primary schools locatedat working area of Primary Health Care Bandar Khalipah Percut Sei Tuan DeliSerdang District.The research method used is descriptive study. The population in this research iselementary school, and the source of information are the UKS teachers and officers ofthe primary health care. The object of the research is primary school. Data wereanalysed using univariate analysis.The Result of this study showed that 63.0% the primary school has a goodprogram planning UKS, the primary school got training by 66.7% and 70.4% theprimary school have good supervising. 53.8% did not reach the health achievementtarget.It is recommended to give capacity building in planning and training as well asalways maintaining good cooperation across program and between public or privatesectors for the improvement of the UKS program in the future.Keywords : UKS, Supervising, Target, Environment Health